What can a New Keynesian labor matching model match? - Christopher Phillip Reicher (Kiel Institute for the World Economy (IfW), 2009)
A labor matching model with nominal rigidities can match short-run movements in labor's share with some success. However, it cannot explain much of the behavior of employment, vacancies, and job flows in postwar US data without resorting to additional shocks beyond monetary policy and productivity shocks. In particular, the model suggests that monetary policy shocks can account for only a small portion of postwar fluctuations, except for the Volcker and late-1940s episodes. Productivity shocks can account for some of the pattern in labor's share and in employment between the late 1960s and the early 1980s. Based on the timing of observed fluctuations in interest rates, inflation, and productivity, it appears that the vast majority of observed fluctuations in the real economy remain unexplained by standard real and nominal shocks.
Keywords: E24; E32; E52; J64; 330; Unemployment; labor market search; job flows; labor share; inflation; productivity shocks; monetary shocks; Arbeitsmarkttheorie; Ungleichgewichtstheorie; Matching; Schock; Theorie der Arbeitslosigkeit; Arbeitsuche; Arbeitsmobilität; Theorie; Schätzung; USA